Manajemen Stress Pada Masa New Normal dalam Menumbuhkan Kesehatan Mental - Nihayah, Ulin; Novita, Dewi; Qurotal Aini, Luk Luk; Qodli, Agisna Asmara (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2022)
Mental health or what we know as mental health is a condition in which the mind of each individual is in a state of peace and calm, so that it will allow each individual to enjoy life that is lived daily and be able to appreciate other individuals who are around him around. The purpose of making this journal is to find out stress management in the new normal period in growing mental health. This study was conducted to determine the extent to which the impact of COVID-19 which interferes with individual mental health has an impact on the stress experienced by many individuals. This study uses the method used in this study, namely using qualapriktive research methods with literature study data collection techniques. Which will discuss 7 national journals which all have something to do with mental health as a result of COVID-19